Role of Multisection CT Angiography in the Evaluation of Vertebrobasilar Vasospasm in Patients with Subarachnoid Hemorrhage - Goldsher, Dorith (AJNR Am J Neuroradiol, 2004)
BACKGROUND AND PURPOSE: Optimal means for assessing cerebral vasospasm, mainly at the vertebrobasilar system, have not been established. The purpose of this study was to evaluate the role of multisection CT angiography (MCTA) in the detection and quantification of vertebrobasilar vasospasm (VBS) indicated on transcranial Doppler (TCD) imaging in patients with subarachnoid hemorrhage (SAH). METHODS: Forty-three MCTA studies of the vertebrobasilar arteries were performed with a multisection spiral CT scanner in 36 patients with SAH. Parameters used were 1-mm collimation, 0.625Q pitch, 120 kV, and 250 mAs. Contrast material was injected (80–100 mL, 3 mL/s) after a 15–20-second delay. Postprocessing of the vertebrobasilar system was performed by using maximum intensity projection and volume-rendering reconstruction. Vessel diameter was measured at different intracranial locations along the vertebral and basilar arteries perpendicular to their long axis by using curved reformatted multiplanar reformation. TCD imaging of the posterior circulation was performed within 24 hours. RESULTS: MCTA demonstrated narrowed arteries compatible with VBS in 13 patients, consistent with TCD findings. Despite TCD recordings of high flow velocity in three other patients, MCTA did not reveal vasospasm but did show wide arteries feeding arteriovenous malformations in two and normal-sized arteries in one. VBS in two patients was identified on MCTA but overlooked during TCD imaging. Twenty patients had normal findings on both TCD and MCTA studies. CONCLUSION: Cerebral MCTA is recommended as a reliable, rapid, and minimally invasive diagnostic method, one complementary to TCD imaging for assessing VBS in patients with SAH.